Learning to teach English in the secondary school : a companion to school experience - Davison, Jon, 1949-; Daly, Caroline (New York : Routledge, 2014)
How do you approach teaching English in the contemporary classroom? What is expected of a would-be English teacher? The fourth edition of this best-selling text combines theory and practice to present an indispensable introduction to the opportunities and challenges of teaching English in the secondary classroom. It offers insight into the history, policies and definitions surrounding the subject, together with innovative and practical strategies which can be used for effective teaching and learning. Already a major text for many university teacher education courses, the new edition reflects the extent and impact of current reforms whilst retaining its focus on what is of enduring value for English teaching.
Contents note continued: introduction -- changes and developments in Advanced Level English -- an overview -- understanding the assessment objectives, knowing your awarding board specification -- classroom approaches -- encouraging independence and developing skills -- alternative interpretations -- the contexts in which texts are written and received -- the Writer's craft -- Language and Literature A Level -- IB, Pre-U and Creative Writing A Level -- summary and key points -- further reading -- 14. Critical Practice / Caroline Daly -- introduction -- student teacher development -- monitoring development -- developing roles and relationships -- reflection -- summary and key points -- note -- further reading.
Includes bibliographical references : (p. 237-246) and index.
Keywords: English language -- Study and teaching (Secondary) -- United Kingdom; English literature -- Study and teaching (Secondary) -- United Kingdom; English teachers -- Training of -- United Kingdom; United Kingdom